Kepentingan Pemerintah Kanada Bergabung Dalam Trans-Pacific Partnership (TPP) Tahun 2011-2016 - Dewi, Ni Putu Trisna; Kumala Dewi, Putu Ratih; Resen, Putu Titah Kawitri (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 4 No 4 (2025): JURNAL DIKSHI, 2025)
This study aims to describe The Canadian Government’s interest in joining the Trans-Pacific Partnership (TPP) in 2011 to 2016 using qualitative-descriptive research methods. This study uses one theory and one concept, there is the Neoliberal-Institusionalism theory and concept of international cooperation. This study  focuses on what is in Canada’s primary interest in joining the TPP despite the resistance, obstacles and economic losses that such participation would incur. Neoliberal-Institusionalism theory helps researchers to see how Canada’s strategy is to involve itself in TPP cooperation in an effort to fulfil its national interest. The concept of international cooperation helps researchers to explain in more detail the purpose of Canada joining TPP. TPP is the first free trade agreement that connects countries in the Asia Pacific and Latin America regions. Canada’s interest in joining the TPP is not necessarily an interest in the economic field only, but also interest in other fields, such as interests in political and strategic fields. Canada’s political and strategic interests in its participation in TPP coorperation include; establishing and re-strengthening diplomatic relations with China, and establishing cooperation with ASEAN member countries, especially  countries that have not joined yet in the CPTPP, such as Indonesia and Thailand through the Strengthening and Expansion of the CPTPP. Keywords : Canada, CPTPP, Neoliberal-Institusionalism, Strategic Interest, TPP